Efficacy of Doxycycline as Monotherapy or in Combination with Levofloxacin in Treating Late-Stage Systemic Anthrax in Non-Human Primates - Amir Ben-Shmuel; Assa Sittner; Itai Glinert; Elad Bar-David; Josef Schlomovitz; Haim Levy; Shay Weiss (International Journal of Translational Medicine, 2026)
Background: Bacillus anthracis spores pose a major biosecurity threat, in light of their use in several documented bioterror attacks and the fact that it was weaponized. The absence of specific and accurate treatment instructions in the 2001 anthrax letter attacks and the poor prognosis of patients receiving ineffective treatment emphasized the need for reliable guidelines for treating exposed (prophylaxis) or symptomatic populations. The recent 2023 CDC guidelines for treating systemic anthrax recommend a combined treatment of a tetracycline (minocycline or doxycycline) with meropenem or a fluoroquinolone. These recommendations differ from the 2001 and 2015 updates, and in the absence of significant clinical data, rely on animal studies. Previously, we demonstrated, based on a rabbit model, that these recommendations are effective in treating various stages of anthrax, ranging from post-exposure prophylaxis to systemic involvement and involvement of the CNS. Methods: We used a trigger-to-treat type of experiment using non-human primates (NHP) infected by nasal spray of a lethal dose of B. anthracis spores. Results: We confirmed our rabbit results by demonstrating the efficacy of doxycycline as a monotherapy or in combination with levofloxacin in treating late-stage systemic anthrax in non-human primates (NHP), in a trigger-to-treat type of experiment. Our experiments show high efficacy of the mono or combined therapy. Conclusions: Our results support the CDC guidelines placing doxycycline as first-choice therapeutics by demonstrating the efficacy of using it as a monotherapy or in combination with levofloxacin, in a second highly relevant NHP model.